Sustainable drinking water: Aila's enduring effects - Khan, A. S. Moniruzzaman; Ahmed, Minhaz Farid (The Daily Star, 2014)
The authors are affiliated with the Centre for Climate Change and Environmental Research (C3ER), BRAC University.